Analysis of the Impact of Digital Payment Platforms on Financial Management During the Covid-19 Pandemic (Case Study of ITB Students) - Ernawati, Ernawatii; Putri, Salma Indira; Azzahra, Tabina (FKIP Universitas Lampung, 2023)
When the Covid Pandemic hit, many changes occurred in human life. Various activities in everyday life had to be limited. including one of them in the payment transaction. Digital payments are one of the solutions that are considered the safest during a pandemic. Digital payments are very popular, especially among the younger generation, including ITB students. Students have made transactions using digital payment platforms, such as Go-Pay, OVO, mobile banking, and so on. Students have a fairly high intensity in using digital payment platforms, especially in shopping transactions of 85%. In terms of purchase transactions, food & beverage purchase transactions are in first place, and clothing and shoes purchase transactions are in second place. Ease of payment, and feeling more comfortable, as well as promos and discounts, are the three main reasons for using digital payment platforms. However, the use of digital payment platforms does not make students better at managing finances. With a digital payment platform, students become increasingly consumptive. However, digital payment platforms are very helpful in tracking expenses and income.Keywords: Digital Payment Platform, Financial Management, ITB Students, Covid - 19 PandemicDOI: http://dx.doi.org/10.23960/E3J/v6i1.50-55